(untitled) (Bangladesh Journal of Agricultural Research, 2012)
A study was conducted to examine the impact of power tillers (PTs) on profitability of Boro rice based cropping patterns in some selected areas of Bangladesh in 2003. Six major Boro rice based cropping patterns out of 23 patterns in the study areas were examined to estimate the profitability differences among the power tiller and draught animal using farms round the year. Analysis revealed that gross return of MV Boro-MV T. Aus- MV T. Aman pattern is 10.5% higher for PT users than that for draught animal power (DAP) users. The total variable cost is 16.2% lower for PT users than that for DAP users resulting the gross margin 158% higher for PT users. Gross returns of MV Boro-MV T. Aus-LV T. Aman, MV Boro-Fallow- MV T.Aman and MV Boro- MV T.Aman-Mustard, MV Boro-MV T. Aus-Fallow patterns are respectively, 9.7%, 8.1%, 23.4% and 35.3% higher for PT users than that for DAP users. The benefit cost analysis indicates that PT users obtain higher yield, higher gross return and higher BCR from MV Boro-Vegetables-MV T. Aman pattern than those of DAP users. Thus, among all six identified patterns, this pattern is more profitable for PT users. The production cost of all six patterns by PT users is substantially lower than those of DAP users. In general, these six patterns are also found to be more profitable when power tillers are used in place of animal power. Use of power tillers was observed to be associated with higher cropping intensity in the study areas. Bangladesh J. Agril. Res. 37(3): 415-432, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12085